INFLUENCE OF GOVERNANCE PRACTICES ON PROVISION OF SAFE LEARNING ENVIRONMENT IN PUBLIC SECONDARY SCHOOLS IN MAKUENI COUNTY, KENYA - MARY NDUNGE MBUVI (Machakos University Press, 2025)
Governance practices adopted by schools play a key role in ensuring safe learning environment in schools. However, in public secondary schools in Makueni County, the situation is quite different with cases of accidents to learners and staff as well as destruction of school infrastructure being on the rise. Thus, the purpose of this was to investigate the influence of governance practices on provision of safe learning environment in public secondary schools in Makueni County, Kenya. The objectives were; assessing the influence of compliance with safety standards and guidelines, stakeholder participation and in-service training programmes on provision of safe learning environment. The study was guided by the Maslow’s Hierarchy of Needs Theory. The study adopted mixed methodology and applied quantitative and qualitative approaches A descriptive research design was employed to collect and analyze data using questionnaires and interview guides. The target population comprised 400 principals, 3769 teachers and 5600 members of school BoM in public secondary schools in Makueni County totaling 9769 respondents from which a sample of 379 respondents was obtained using Yamane’s Formula. Stratified sampling was used to create nine strata based on the number of sub-counties in Makueni County From each sub-county, five principals and 20 members of school BoM were selected using purposive sampling. However, simple random sampling was applied to select 26 teachers. Questionnaires were used to collect quantitative data from teachers whereas interview guides were used to collect qualitative data from principals and members of school BoM. There was also document checklist analysis guide for the researcher. Piloting was conducted among 38 respondents from a sample of public secondary schools in Makueni County to establish validity and reliability. Validity was ascertained with the help of university supervisors and experts in educational administration. Reliability was determined using split-half technique and a reliability index, r = 0.725, between two ‘halves’ was obtained using Cronbach Alpha Method, which indicated high internal reliability. Data analysis began by identifying common themes. Qualitative data were analyzed thematically along the study objectives and presented in narrative forms. Quantitative data were analyzed using descriptive statistics such as frequencies and percentages. Statistical Packages for Social Science (SPSS Version 29) was used to analyse data was presented using tables and percentages. The study revealed that provision of a safe learning environment poses significant challenges in many public secondary schools. Many of these schools have reported various incidents of accidents and injuries affecting both staff and students, alongside recurrent damage to physical facilities. This is partly attributed to the failure of such public secondary schools to adhere to safety standards and guidelines, rare stakeholder participation as well as irregular in-service training programmes on how to create safe learning environment in schools. Thus, the study recommends that principals should ensure that schools comply with safety standards and guidelines, establish a structured safety audit and monitoring system to ensure continuous compliance with safety standards and guidelines. They should actively engage all stakeholders in collaborative decision making to ensure a safe learning environment. Principals should regularly conduct specialized training sessions on conflict resolution, mental health awareness and emergency preparedness for staff and students.